An exploratory study of social selling on LinkedIn: the concept and its implications - Bilro, R.G.; Loureiro, S. M. C. (ICMarktech'20, 2020)
Due to the digital transformation, the purchasing process is evolving, rising the need to reinvent the sales process. Through marketing and sales tools and tactics, social selling presents itself as a strategy that supports the company to position itself at the beginning of consumers journey. It also allows firms t retake its influence in the decisionmaking process, through the education of customers, building and strengthening relationships based on trust, customized customers strategies and generation of value and content. Through a qualitative methodology using in-depth interviews, this research aims to shed light on a topic that is still under-explored and to propose the application of this strategy in firms. From this study, both theoretical and managerial implications are offered.